Hypothalamic AMPK as a Regulator of Energy Homeostasis - My Khanh Q. Huynh (Neural Plasticity, 2016)
Activated in energy depletion conditions, AMP-activated protein kinase (AMPK) acts as a cellular energy sensor and regulator in both central nervous system and peripheral organs. Hypothalamic AMPK restores energy balance by promoting feeding behavior to increase energy intake, increasing glucose production, and reducing thermogenesis to decrease energy output. Besides energy state, many hormones have been shown to act in concert with AMPK to mediate their anorexigenic and orexigenic central effects as well as thermogenic influences. Here we explore the factors that affect hypothalamic AMPK activity and give the underlying mechanisms for the role of central AMPK in energy homeostasis together with the physiological effects of hypothalamic AMPK on energy balance restoration.